Aminocyclopyrachlor and mesotrione sorption–desorption in municipal sewage sludge-amended soil - Mendes,Kassio Ferreira (2019)
ABSTRACT The application of sewage sludge (SS) in agriculture is a practice used worldwide, and it is commonly applied in sugarcane to supply nutrients, with beneficial effects on crop productivity and soil; but SS can increase sorption and decrease desorption of herbicides. However, in tropical soils such as in Brazil, there are no studies regarding the behavior of pre-emergent herbicides, mainly aminocyclopyrachlor and mesotrione, in SS-amended soil. The aim of the present study was to determine the effect of municipal SS applied in agriculture on the sorption–desorption of aminocyclopyrachlor and mesotrione in clay soil. Aminocyclopyrachlor (pyrimidine-2-14C-aminocyclopyrachlor) and mesotrione (cyclohexane-2-14C-mesotrione) sorption–desorption was evaluated using a batch equilibrium method. Soil was amended at 0% (control – unamended), 0.1%, 1%, and 10% (w∙w–1) of air-dried SS corresponding to 1.2, 12, and 120 t∙ha–1. The Freundlich Kf sorption values of aminocyclopyrachlor and mesotrione were similar for all treatments, ranging from 1.07 to 1.45 and 3.48 to 4.25 µmol (1–1/n) L1/n∙kg–1, respectively. Overall, the lowest Kd sorption value of these herbicides was reported for SS-amended soil (1%), while in the SS-amended soil (10%) it was higher than unamended soil. The H value for aminocyclopyrachlor was ~1 (no hysteresis) and for mesotrione was on average 0.4 (hysteresis occurring). In conclusion, the present study indicates that SS applied in any crop to supply nutrients can slightly affect the sorption–desorption of aminocyclopyrachlor and mesotrione, but this small difference does not affect the bioavailability of these herbicides for weed control.